Implementasi Model Project Based Learning pada Mata Pelajaran IPAS Sebagai Proyek Penguatan Profil Pelajar Pancasila Siswa Kelas IV SDN Dukuh Kupang V Surabaya - Tyastuti, Setya Ridia Cahyaning Dewi; Suprihatien, Suprihatien; Pratiwi, Desi Eka (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Basic education plays a crucial role in shaping students' character, not only in terms of cognitive intelligence but also through the development of spiritual, emotional, social, and moral values in accordance with the Pancasila Student Profile Strengthening Project. However, in reality, learning in elementary schools often remains monotonous and lacks active student participation, especially in the subject of Natural and Social Sciences (IPAS). This study aims to describe the implementation of the Project-Based Learning (PjBL) model as a strategy to strengthen the collaborative and creative dimensions of the Pancasila Student Profile. This research employed a descriptive qualitative approach through a case study in class IVA at SDN Dukuh Kupang V Surabaya. Data were collected through observation, questionnaires, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results showed that the implementation of the PjBL model using diorama media successfully increased student engagement in the learning process. Group projects fostered a sense of collaboration and creativity among students in understanding the diversity of Indonesian culture. Moreover, this model created a more enjoyable learning atmosphere and improved student motivation.